Preparation and in vitro characterization of paclitaxel-loaded injectable microspheres - Hiremath, Jagadeesh G; Devi, V Kusum (Asian Journal of Pharmaceutics (AJP), 2014)
The main objective of this study was to develop paclitaxel loaded poly (caprolactone) injectable microspheres prepared by solvent evaporation method. Mircoparticles were characterized in terms of particle size and size distribution, surface morphology, drug physical state, and crystalline nature by using master size analyzer, scanning electron microscope,differential scanning calorimetry, and X-ray diffraction. Paclitaxel loading over different concentrations was analyzed by high-performance liquid chromatography. In vitro drug release studies were performed in phosphate buffer saline. Best formulation was selected for in vitro cytotoxic studies by using MCF-7 breast cancer cell lines.